2016
DOI: 10.1061/(asce)wr.1943-5452.0000571
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal Operation of the Multireservoir System in the Seine River Basin Using Deterministic and Ensemble Forecasts

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Correspondence to: andrea.ficchi@irstea.fr 2 AbstractWe investigate the improvement of the operation of a four-reservoir system in the Seine River basin, France, by use of deterministic and ensemble weather forecasts and real-time control. In the current management, each reservoir is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
(44 reference statements)
1
51
0
Order By: Relevance
“…Results for the case study demonstrated that some of the specific approaches that were tested could be useful for real-time reservoir operation. Ficchì (2015) presented a study where authors aimed to investigate the improvement of a four-reservoir operation system in the Seine River basin, France, using an ensemble of weather forecasts and a real-time control approach. In the proposed system, a model predictive control (MPC) optimization technique was used, and it was modified to a version that incorporated uncertainties in the form of a tree-based model predictive control (TB-MPC) approach in order to account for deterministic and ensemble forecasts, respectively.…”
mentioning
confidence: 99%
“…Results for the case study demonstrated that some of the specific approaches that were tested could be useful for real-time reservoir operation. Ficchì (2015) presented a study where authors aimed to investigate the improvement of a four-reservoir operation system in the Seine River basin, France, using an ensemble of weather forecasts and a real-time control approach. In the proposed system, a model predictive control (MPC) optimization technique was used, and it was modified to a version that incorporated uncertainties in the form of a tree-based model predictive control (TB-MPC) approach in order to account for deterministic and ensemble forecasts, respectively.…”
mentioning
confidence: 99%
“…Their performance has been found to be superior to regression (Bessler et al, ); and similar to ANNs (Senthil Kumar et al, ) and BNs (Sherafatpour et al, ). They have also been used to forecast future inflows to be used by optimization algorithms (Castelletti et al, ; Chazarra et al, ; Côté & Leconte, ; Ficchì et al, ; Housh, Ostfeld, & Shamir, ).…”
Section: Rule Inference From Optimization Resultsmentioning
confidence: 99%
“…Main options for inflow forecasting in Model Predictive Control Inflow forecasting approach Examples of applications Hydrologic and/or hydraulic models forced with meteorological forecasts Bianucci, Sordo-Ward, Moralo, and Garrote(2015), Caseri, Javelle, Ramos, and Leblois (2016),Côté and Leconte (2015),Faber and Stedinger (2001),Ficchì et al (2015),Pianosi and Ravazzani (2010),Raso, Schwanenberg, van de Giesen, and van Overloop (2014) …”
mentioning
confidence: 99%
“…The four reservoirs in the system are operated independently and follow filling curves that determine the target amount of water retained in the reservoir each 30 day of the year. During the high flow seasons of November -June they store water in order to maintain low flows during the upcoming dry season, a necessary function to regulate water levels for shipping and drinking water to approximately 20 million people, among other socio-economic benefits (Ficchì et al, 2016;Dorchies et al, 2014). During this flooding event, all of the reservoirs were near 90% full in anticipation of typically dry conditions in the summer months.…”
mentioning
confidence: 99%